Wydział Teologiczny Uniwersytetu Kardynała Stefana Wyszyńskiego w Warszawie - Bartnicki, Roman (Studia Nauk Teologicznych PAN, 2020)
Th e Faculty of Th eology of Cardinal Stefan Wyszyński University in Warsaw is endowed with rich history. It existed at the Royal University of Warsaw, established in 1816.It operated until the University was closed in 1831; then its activity was continued at the Main Seminary (1823–1835), and fi nally at the Roman-Catholic Clerical Academy (1835–1867). Th e Th eological Faculty came into being again at the University of Warsaw in 1918. Aft er the World War II, the faculty became active in 1945, in 1954 it became part of the Academy of Catholic Th eology and since 1999 it has been included into the Cardinal Stefan Wyszyński University. Th e achievements of the faculty are important, it has employed many eminent theologians and instructed thousands of graduates. Its merits for the Church and Polish culture are not to be neglected. Th e following scientifi c grades in theology were awarded at the Th eological Faculty of the Academy of Catholic Th eology (1954–1999): 85 professional bachelor’s degrees, 4853 master’s degrees, 762 canonical licentiates, 313 doctor’s degrees, 92 nostrifi cations of doctorates and 89 post-doctoral degree. Th e following scientifi c grades in theology have been awarded at the Th eological Faculty of Cardinal Stefan Wyszyński University (from 1 October 1999 to 16 June 2008): 3916 bachelor’s degrees, 5718 master’s degrees, 1315 canonical licentiates, 299 doctor’s degrees, 71 nostrifi cations of doctorates, 45 post-doctoral degrees and 23 professor’s degrees in theology. In addition, the Institute of Studies of the Family has awarded 1733 master’s degrees in studies of the family. Nowadays, the Th eological Faculty of Cardinal Stefan Wyszyński University is composed of six institutes: Institute of Th eology, Institute of Media Education and Journalism, Institute of the Studies of Culture, Institute of Th eology in Radom, Institute of Apostleship Th eology, Institute of Studies of the Family. Th e Th eological Faculty includes as well the Non-local Didactical Centre in Gdynia. Th ree clerical seminaries are affi liated at the Th eological Faculty: Higher Clerical Seminary in Płock, Gdańsk Clerical Seminary in Gdańsk-Oliwa, Higher Clerical Seminary of Catholic Apostleship in Ołtarzew. Th e following institutions are bound with the Faculty of Th eology of the Cardinal Stefan Wyszyński University with the cooperation agreement: Archdiocese Clerical Seminary in Białystok, Higher Clerical Seminary in Łódź, Higher Clerical Seminary in Łomża, Franciscan Higher Clerical Seminary in Łódź-Łagiewniki, Higher Clerical Seminary of the Salesian Society in Ląd nad Wartą, Higher Clerical Seminary of the Salesian Society in Łódź.